Challenges in Understanding the Variability of the Cryosphere in the Himalaya and Its Impact on Regional Water Resources - Vishwakarma, Bramha Dutt; Ramsankaran, RAAJ; Azam, Mohd. Farooq; Bolch, Tobias; Mandal, Arindan; Srivastava, Smriti; Kumar, Pankaj; Sahu, Rakesh; Navinkumar, Perumal Jayaraman; Tanniru, Srinivasa Rao; Javed, Aaquib; Soheb, Mohd; et al. (Frontiers in Water, 2022)
The Himalaya plays a vital role in regulating the freshwater availability for nearly a billion people living in the Indus, Ganga, and Brahmaputra River basins. Due to climate change and constantly evolving human-hydrosphere interactions, viz., land use/cover changes, groundwater extraction, reservoir or dam construction, etc., the water availability has been and is expected to change considerably in the future. Therefore, understanding the spatio-temporal evolution of the hydrological cycle over the Himalaya and its river basins has been one of the most critical exercises towards ensuring regional water security. However, due to the lack of extensive in-situ measurements, complex hydro-climatic environment, and limited collaborative efforts, large gaps in our understanding exist. Moreover, there are several significant issues in available studies, such as lack of consistent hydro-meteorological datasets, very few attempts at integrating different data types, limited spatiotemporal sampling of hydro-meteorological measurements, lack of open access to these datasets, poorly accounted anthropogenic climate feedbacks, and limited understanding of the dominant drivers of the hydro-meteorological variability over the region. These factors result in large uncertainties in our estimates of current and future water availability over the Himalaya, which constraints the development of sustainable water management strategies for its river catchments hampering our preparedness for the current and future changes in hydro-climate. To address this critical issue, a partnership development workshop entitled "Water sEcurity assessment in rIvers oriGinating from Himalaya (WEIGH)", was conducted between the 07th and 11th September 2020. Based on the intense discussions and deliberations among the participants, the most important and urgent research questions were identified. This white paper synthesizes the current understanding, the most significant research gaps and research priorities of the water resources linked with the Himalayan rivers and its basins.